Aspectos sociales y culturales de la educación matemática - Bishop, Alan J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper deals with two fields of research which have contributed to revise the teaching of Mathematics over the last decade: those concerned with social and cultural aspects of Mathematics education.